HUBUNGAN STIMULASI IBU DENGAN PERKEMBANGAN MOTORIK PADA ANAK USIA 3-5 TAHUN DI PENDIDIKAN ANAK USIA DINI - Suyanti Suwardi (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: According to WHO 2018, the problem of child development is increasing, the incidence rate in the United States ranges from 12-16%, Argentina 20%, Thailand 37.1%, and in Indonesia between 13-18%. Looking at the epidemiological data, it is necessary early detection and intervention in children with developmental disorders. Aceh Profile data in 2019 the percentage of health service coverage for children under five years of age has a effect, namely that 65% of the health of children under five must be monitored to ensure that their health is always in optimal condition.The Purpose: Research to determine the relationship between maternal stimulation on motor development in children aged 3-5 years in Paud INARA, Johan Pahlawan District, West Aceh Regency, 2020